Formulation of Iḥdād Rights for Career Women in Counter Legal Draft Compilation of Islamic Law - Sohrah; Ridwan, M. Saleh; Musrianaa (Parewa Saraq: Journal of Islamic Law and Fatwa Review, 2022)
This study aims to analyze and formulate applicable ihdad rights for career women within the framework of the Counter Legal Draft Compilation of Islamic Law. Counter Legal Draft KHI is a legal product of Islamic law reform in Indonesia. The material contained in the KHI is considered gender bias against women, so CLD-KHI was born which aims to revise the article on gender bias in the KHI. With one of the approaches used in formulating laws based on gender equality so that the role of women in society that has undergone significant evolution, including in terms of education, career, and active participation in economic life does not reduce women's rights. This research is classified as library research type, data is collected by reviewing and reviewing various books that have relevance to the subject matter, and then using primary and secondary data sources, with normative analysis research methods on various sources of Islamic law, legal documents, and related literature. This research also involves a comparative approach to compare the views of different schools of Islamic law regarding ihdad rights and their context in the lives of career women today. The results showed that it is necessary to reformulate ihdad rights in order to accommodate the aspirations and real conditions of career women. This reformulation should take into account just and balanced inheritance rights, without neglecting fundamental principles of Islamic law. In addition, it is also necessary to integrate social, economic, and cultural aspects in consideration of the formulation of new ihdad rights. This research contributes in the face of social change and the demands of gender equality in the context of Islamic law. It is hoped that the resulting ihdad rights formulation can provide guidance for legislators and legal practitioners in developing more inclusive and fair regulations for career women, while adhering to fundamental Islamic legal principles.